Fast and sensitive delineation of brain tumor with clinically compatible moxifloxacin labeling and confocal microscopy. Issue 1 (18th August 2019) - Lee, Seunghun; Park, Won Yeong; Chang, Hoonchul; Kim, Bumju; Jang, Won Hyuk; Kim, Seonghan; Shin, Younghoon; Kim, Myoung Joon; Lee, Kyung Hwa; Kim, Eui Hyun; Chung, Euiheon; Kim, Ki Hean
Abstract: Delineation of brain tumor margins during surgery is critical to maximize tumor removal while preserving normal brain tissue to obtain optimal clinical outcomes. Although various imaging methods have been developed, they have limitations to be used in clinical practice. We developed a high‐speed cellular imaging method by using clinically compatible moxifloxacin and confocal microscopy for sensitive brain tumor detection and delineation. Moxifloxacin is a Food and Drug Administration (FDA) approved antibiotic and was used as a cell labeling agent through topical administration. Its strong fluorescence at short visible excitation wavelengths allowed video‐rate cellular imaging. Moxifloxacin‐based confocal microscopy (MBCM) was characterized in normal mouse brain specimens and visualized their cytoarchitecture clearly. Then, MBCM was applied to both brain tumor murine models and two malignant human brain tumors of glioblastoma and metastatic cancer. MBCM detected tumors in all the specimens by visualizing dense and irregular cell distributions, and tumor margins were easily delineated based on the cytoarchitecture. An image analysis method was developed for automated detection and delineation. MBCM demonstrated sensitive delineation of brain tumors through cytoarchitecture visualization and would have potentials for human applications, such as a surgery‐guiding method for tumor removal. Abstract : In brain tumor surgery, complete resection of tumor tissue while preserving normal brain tissue is critical to obtain an optimal clinical outcome. A high‐speed cellular imaging method using clinically applicable moxifloxacin labeling, called as moxifloxacin based confocal microscopy (MBCM), was developed for fast and sensitive tumor detection and delineation. MBCM distinguished brain tumors from normal brain based on cytoarchitectural difference, and would have potentials as a surgery‐guiding method.